Failure Analysis of High-Pressure Turbine Blades in Steam Power Plants - Anggit Aji Purnomo; Sunaryo Sunaryo; Ahmad Kafrawi Nasution (AMTS and Faculty of Engineering - Universitas Riau, 2022)
This paper describes the failure of high-pressure steam turbine blades. During the Serious Inspection, it was discovered that the ninth-stage high-pressure turbine blade had failed. The causes of blade failure are examined via visual inspection and destructive testing. The failure mechanism of the blades was determined by conducting mechanical properties testing, metallographic inspection, and energy spectrum analysis. The mechanical properties of the leaf and root blade specimens were within the range of blade steel for steam turbines according to the Chinese National Standard (GB/T 8732-2004), but the chemical composition was not identical. This is consistent with the root blade fracture pattern where the hardness value plotted from the test results is the lowest at the root blade location, which is the primary cause of fissure propagation.